Plausibility criteria for putative pathophysiological mechanisms in functional gastrointestinal disorders: a consensus of experts - Tack, Jan; Corsetti, Maura; Camilleri, Michael; Quigley, Aaron; Simren, Magnus; Suzuki, Hidekazu; Talley, Nicholas J.; Tornbloom, Hans; Van Oudenhove, Lukas (BMJ Publishing Group, 2017)
The functional gastrointestinal disorders (FGIDs), are extremely common conditions associated with a considerable personal, social and health economic burden. Managing FGIDs in clinical practice is challenging because of the uncertainty of symptom-based diagnosis, the high frequency of overlap between these conditions and the limited efficacy of available therapies. It has often been argued that successful drug development and management of FGIDs requires knowledge of the underlying pathophysiology. Numerous and highly variable candidate pathophysiological mechanisms have been implicated in the generation of FGID symptoms, but there is no current consensus on how to best define the relevance of these disturbances. Methods: A group of international experts on FGIDs developed plausibility criteria that should be fulfilled by relevant pathophysiological mechanisms in FGIDs. Results: Five criteria are proposed: 1) presence of the abnormality in a subset of patients; 2) temporal association between proposed mechanism and symptom(s); 3) correlation between the level of impairment of the mechanism and symptom(s); 4) induction of the symptom(s) by provoking the pathophysiological abnormality in healthy subjects and 5) treatment response by a therapy specifically correcting the underlying disorder, or congruent natural history of symptoms and dysfunction in the absence of specific therapy. Based on strength of evidence for these 5 criteria, a plausibility score is proposed. Conclusion: Evaluation of the strength of evidence for candidate pathophysiological abnormalities fulfilling these 5 plausibility criteria will help to identify the most relevant mechanisms to target for novel diagnostic approaches and for the development of new therapies.